Food for Spain : inter-departmental correspondence - Bolton, W. J.
030-0067-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From W. J. B0LT0N. Department INTERNATIONAL. To SIR WALTER CITRINE. Date 14th September 1938. SUBJECT. FOOD FOR SPAIN. Mr. Tewson 'phoned yesterday (13. 9. 38). Scottish T.U.C. suggest International Solidarity Fund should buy 200 tons of foodstuffs (cost about £2,500) to add to consignment of 300 tons they are sending to Spain freight free. Are you agreeable? I agree. WC 292/946/30/67